THE USE OF NON-TRADITIONAL TEACHING METHODS IN THE METHODOLOGICAL TRAINING OF FUTURE PRIMARY SCHOOL TEACHERS (International journal of artificial intelligence, 2025)
This article explores the theoretical and practical aspects of applying modern, innovative, and digitally-based non-traditional teaching methods in the methodological training of future primary school teachers. The study introduces new methodological approaches such as “digital reflection”, “virtual collaboration”, “AI-assisted teaching”, “gamified methodological training”, and “micro-teaching simulator”, which correspond to the educational trends of 2025. These approaches aim to enhance future teachers’ competencies in independent thinking, rapid problem-solving, effective use of digital tools, and creative methodological decision-making. Moreover, the paper proposes a new model for analyzing and improving methodological training through artificial intelligence support.